A transparent polyether-polycarbonate-polyamide block copolymer and a method for preparing and using the same

CN122978433APending Publication Date: 2026-10-27NANJING UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510536359.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但该方法需两步进行,聚酰胺预聚体的合成需在去离子水中加热溶解、调节pH值、加压1.0~1.8MPa,以及减压至常压后抽真空等操作,聚醚二元醇与环状内酯也需在另一反应釜中加压反应,该方法合成过程复杂,成本较高

Benefits of technology

[0048]1、首先,本发明所述的透明聚酰胺热塑性弹性体,硬链段以己内酰胺作为主要原料,通过开环聚合生成具有密集酰胺基团分布的线性链段,并利用一定比例的长碳链二元酸和脂肪环二元胺进行共聚,在维持必要氢键交联密度的同时,破坏了单一聚己内酰胺结晶规整度,避免了聚酰胺硬链段因结晶度高而造成的透光率下降问题,使材料保持高透明性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978433A_ABST
    Figure CN122978433A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high transparent polyether-polycarbonate-polyamide block copolymer and its preparation method and application, belong to material field.The application proposes a kind of block copolymer elastomer material, which is obtained by copolymerization of caprolactam, aliphatic cyclic diamine and long carbon chain dibasic acid as raw material, with polyether dihydric alcohol and polycarbonate dihydric alcohol as soft segment.The block copolymer elastomer material meets the light transmittance, and has excellent mechanical properties.The transparent polyether-polycarbonate-polyamide block copolymer is obtained by direct melt polymerization, the main synthetic raw material is easy to obtain, the synthesis method is simple, and industrial production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials, and particularly relates to a transparent polyether-polycarbonate-polyamide block copolymer elastomer and its preparation method. Background Technology

[0002] Polyether block polyamide thermoplastic elastomer (TPAE) is a block copolymer composed of alternating hard segments of polyamide and soft segments of polyether or polyester. It has the characteristics of high mechanical strength, good toughness, chemical corrosion resistance and strong heat resistance, and is widely used in sports equipment, medical devices, automotive parts, electronics and electrical appliances and other industries.

[0003] TPAEs typically have a two-phase structure in their microstructure. High-melting-point, crystalline polyamide segments act as the dispersed phase, aggregating into many tiny physical cross-linked regions. This results in strong association between the molecular chains, providing TPAEs with mechanical strength. Meanwhile, non-crystalline polyether soft segments with greater free rotation capability act as the continuous phase, distributed around the micro-regions, providing TPAEs with elastic deformation capabilities.

[0004] However, the microscopic phase separation structure of TPAE also makes it easy for light to be refracted at the interface between the two phases. At the same time, the excessively large size of the crystal micro-regions, which exceeds the wavelength of visible light, will also hinder the propagation of light. This results in TPAE usually appearing as translucent or milky white, which limits its application in high-speed rail, airplane and ship portholes, transparent medical catheters, and sports goggles.

[0005] In the currently disclosed methods for synthesizing transparent TPAE, long-chain diacids and diamines are mainly used, with at least one of them having an aliphatic ring structure, to synthesize polyamide segments with weak crystallinity. Polyethers or polyesters are then copolymerized with these segments as soft segments to obtain TPAEs with good transparency.

[0006] Patent CN 108299639 A synthesizes transparent polyether block polyamide thermoplastic elastomers using diamines, diacids, caprolactam, polyethers, or polyetheramines as main raw materials. At least one of the diamines and diacids contains a cyclohexane structure. However, the method uses excessively high amounts of polyether or polyetheramine, resulting in a low density of hard-segment hydrogen bond crosslinking. This makes the material too soft overall; the highest hardness in the examples is only 40D, and the highest glass transition temperature is only -65°C, making it difficult to apply in situations requiring high hardness.

[0007] Patent CN 113429568 A describes a method that uses a diacid and an alicyclic diamine to generate a transparent nylon salt. Then, using polyether as the soft segment, the polyether product is introduced into the transparent nylon synthesis process to prepare a transparent polyether block polyamide thermoplastic elastomer. However, all the examples disclosed in this method use polybutanediol as the polyether segment, and the content is too high, accounting for 25 wt% of the entire transparent nylon elastomer. Its elongation at break is only 210%, and its transparency is only 65%, resulting in poor elasticity and optical properties.

[0008] Patent CN 118755094 A describes a two-step synthesis of a transparent polyamide elastomer material: first, a carboxyl-terminated polyamide hard segments are obtained by copolymerizing an aliphatic cyclic diamine, an aliphatic linear diamine, and an aliphatic linear dicarboxylic acid; then, a polyether diol and a cyclic lactone are reacted in a polymerization reactor for 1–2 hours; finally, the carboxyl-terminated polyamide prepolymer is added to the polymerization reactor and reacted for 2–6 hours to obtain the transparent polyamide elastomer. However, this method requires two steps. The synthesis of the polyamide prepolymer requires heating and dissolving it in deionized water, adjusting the pH value, pressurizing it to 1.0–1.8 MPa, and then reducing the pressure to atmospheric pressure and then evacuating. The polyether diol and the cyclic lactone also need to be reacted under pressure in another reactor. This method is complex and costly. Summary of the Invention

[0009] To overcome the shortcomings of existing technologies, this invention provides a highly transparent polyether-polycarbonate-polyamide block copolymer, its preparation method, and its applications. This material possesses advantages such as high transparency, excellent tensile properties, high hardness, and a high glass transition temperature. Furthermore, the preparation process is simple, the raw materials are readily available, and the production cost is low, which is beneficial for industrial production. The transparent polyether-polycarbonate-polyamide block copolymer of this invention can achieve both high light transmittance and excellent mechanical properties. It can be obtained through direct melt polymerization, the raw materials are readily available, the synthesis method is simple, and it is easy to industrialize.

[0010] To solve the technical problems mentioned above, the technical solution proposed by this invention is as follows: The high-transparency polyether-polycarbonate-polyamide block copolymer is formed by one-pot melt polymerization of caprolactam, long-chain dicarboxylic acid, aliphatic cyclic diamine, polyether diol, and polycarbonate diol PCDL (molecular weight of 500-3000) as raw materials in the presence of ring-opening agent, catalyst, antioxidant, and chain extender 2,2'-(1,3-phenylene)-dioxazoline or 1,4-bis(4,5-dihydro-2-oxazole)benzene. The high-transparency polyether-polycarbonate-polyamide block copolymer has the following structural formula:

[0011]

[0012] In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1It is 2,2'-(1,3-phenylene)-dioxazoline or 1,4-bis(4,5-dihydro-2-oxazol)benzene, R 2 For polycarbonate diol PCDL, A 2 R is a long-chain dicarboxylic acid, represented by 1,10-sebacic acid or 1,12-dodecanoic acid. 1 It is polytetrahydrofuran diol (PTMG) or polyethylene glycol (PEG), A 1 It is 1,4-cyclohexanediamine, isophoronediamine, or 4,4'-diaminodicyclohexylmethane.

[0013] The transparent polyether-polycarbonate-polyamide block copolymer is obtained by one-pot melt polymerization of caprolactam, long-chain dicarboxylic acid, aliphatic cyclic diamine, polyether diol, and polycarbonate diol in the presence of a polymerization catalyst. This polyether-polycarbonate-polyamide block copolymer material has excellent transparency and mechanical properties, and its transparency, hardness, and tensile properties can be adjusted within a certain range. It can be used in various applications such as aircraft or high-speed rail windows, sports goggles, flexible displays, and medical catheters.

[0014] Specifically, the long-chain dicarboxylic acid is a saturated long-chain dicarboxylic acid with ten or more carbon atoms, such as 1,10-sebacic acid, 1,12-dodecanoic acid, etc.; the aliphatic ring diamine is a saturated aliphatic diamine with an aliphatic six-membered ring, such as 1,4-cyclohexanediamine, isophoronediamine, 4,4'-diaminodicyclohexylmethane.

[0015] The polyether diol is hydroxyl-terminated polytetrahydrofuran and hydroxyl-terminated polyethylene glycol, with a molecular weight in the range of 250-1000, and the polycarbonate diol has a molecular weight in the range of 500-3000.

[0016] The polymerization catalyst is a commonly used catalyst in amidation and esterification reactions, namely phosphoric acid and p-toluenesulfonic acid.

[0017] Since the reaction is carried out at a high temperature of around 250°C, a certain amount of antioxidant needs to be added to the material to prevent the polymer from oxidizing and discoloring. The antioxidants are commonly used in the polymerization of polyester and polyamide, such as antioxidant 1076, antioxidant 1010, antioxidant AT168, triphenyl phosphite, or one or more of these.

[0018] The proportions of each main raw material in the synthesis of the above-mentioned transparent polyether-polycarbonate-polyamide block copolymer elastomer are as follows:

[0019] 14.57–21.52 parts of caprolactam; 10.75–14.64 parts of long-chain dicarboxylic acids; 4.00–9.34 parts of alicyclic diamines;

[0020] 4.67 to 7.20 parts of polyether diol; 1.17 to 2.33 parts of polycarbonate diol.

[0021] To ensure the ring-opening efficiency of caprolactam, the amount of deionized water used as the ring-opening agent should be 5.0-6.0% of the mass of caprolactam, and the nitrogen flow rate should be relatively low during the ring-opening step to reduce the loss of water molecules in the system.

[0022] To ensure that the product is not oxidized at high temperatures, the nitrogen flow rate should be stable, the entire device should have good sealing properties, and the amount of antioxidant should be 0.1% to 0.5% of the polymer raw material mass.

[0023] To ensure the efficiency of the esterification reaction, the catalyst dosage is 0.3-0.5% by mass of the polymer raw material. Phosphoric acid and p-toluenesulfonic acid can be combined to achieve better catalytic effect. In addition, the reaction efficiency can be improved by increasing the nitrogen flow rate and speeding up the stirring speed to allow water molecules generated in the esterification reaction to be discharged quickly.

[0024] To ensure that the highly transparent polyether-polycarbonate-polyamide block copolymer has a high molecular weight and a narrow molecular weight distribution, the amount of chain extender is 0.6% to 0.9% of the sum of the amounts of polyether diol and polycarbonate diol, and the molar number of the long-chain dicarboxylic acid should be strictly equal to the sum of the amounts of the aliphatic ring diamine, polyether diol, and polycarbonate diol and half the amount of chain extender.

[0025] Preferably, the polycarbonate diol PCDL has the following structural formula:

[0026] Where y = 2 to 23;

[0027] The chain extender 2,2'-(1,3-phenylene)-dioxazoline has the following structural formula: The structural formula of 4-bis(4,5-dihydro-2-oxazole)benzene is:

[0028] Preferably, the long-chain dicarboxylic acid is one or more of 1,10-sebacic acid or 1,12-dodecanoic acid; the aliphatic cyclic diamine is 1,4-cyclohexanediamine, isophoronediamine, or 4,4'-diaminodicyclohexylmethane; the polyether diol is one or two of polytetrahydrofuran diol (PTMG) or polyethylene glycol (PEG), with a molecular weight of 250-1000; the ring-opening agent is deionized water; the catalyst is one or two of phosphoric acid and p-toluenesulfonic acid; and the antioxidant is one or more of antioxidant AT-168, antioxidant 1010, antioxidant 1076, or triphenyl phosphite.

[0029] Preferably, the mass fractions of each raw material during synthesis are: 14.57–21.52 parts of caprolactam; 10.75–14.64 parts of long-chain dicarboxylic acid; 4.00–9.34 parts of alicyclic diamine; 4.67–7.20 parts of polyether diol; and 1.17–2.33 parts of polycarbonate diol. The amount of the long-chain dicarboxylic acid is equal to the sum of the amounts of the alicyclic diamine, polyether diol, and polycarbonate diol, plus half the amount of the chain extender.

[0030] Preferably, the ring-opening agent is used at a mass fraction of 5.0-6.0% of caprolactam; the chain extender is used at a mass fraction of 0.6%-0.9% of the sum of the amounts of polyether diol and polycarbonate diol; the catalyst is used at a mass fraction of 0.3-0.5% of the polymer raw material; and the antioxidant is used at a mass fraction of 0.1-0.5% of the polymer raw material.

[0031] The preferred optimal performance ratio for achieving high transparency, tensile strength, and elongation at break is: 19.42 parts caprolactam; 13.26 parts 1,10-sebacic acid; 7.00 parts isophorone diamine; 5.84 parts PTMG250; 1.17 parts PCDL3000; 0.97 parts ring-opening agent deionized water; 0.16 parts catalyst phosphoric acid; 0.14 parts antioxidant AT168; and 0.31 parts chain extender 2,2'-(1,3-phenylene)-dioxazoline.

[0032] Preferably, it includes the following steps:

[0033] (1) Add the required caprolactam, long-chain dicarboxylic acid, aliphatic ring diamine, catalyst, ring-opening agent and antioxidant to a 250mL three-necked flask. Under nitrogen protection at a flow rate of 10mL / min, heat to 180-200℃. After the raw materials in the flask are completely melted, start stirring at a speed of 100-120r / min. Maintain this condition for 2 hours. The small molecules produced by the reaction are distilled out through the condenser of the distillation head.

[0034] (2) Add the polyether diol and polycarbonate diol to a three-necked flask, heat to 240-260°C, nitrogen flow rate between 20-40 mL / min, stirring speed between 120-160 r / min, and maintain these conditions to continue the reaction for 2-2.5 hours.

[0035] (3) Add the chain extender to a three-necked flask, heat to 240-260°C, stir at 120-160 r / min, react for 5 min, then turn off the nitrogen gas, adjust the stirring speed to 90-110 r / min, evacuate to the pressure of -0.1 MPa, and continue to react at 240-260°C for 1-2 hours to obtain a highly transparent polyether-polycarbonate-polyamide block copolymer.

[0036] The highly transparent polyether-polycarbonate-polyamide block copolymer can be used in fields such as aircraft or high-speed rail windows, sports goggles, flexible displays, and medical catheters.

[0037] Preferably, the transparent polyether-polycarbonate-polyamide block copolymer is formed by melt polycondensation of caprolactam, isophorone diamine, 1,10-sebacic acid, PTMG250, and polycarbonate diol as raw materials in the presence of ring-opening agent deionized water, catalyst phosphoric acid, antioxidant AT168, and chain extender 2,2'-(1,3-phenylene)-dioxazoline.

[0038] The preferred performance ratio that achieves the highest transparency is Example 5:

[0039] 19.28 parts caprolactam; 13.42 parts 1,10-sebacic acid; 7.00 parts isophorone diamine; 5.84 parts PTMG250; 1.17 parts PCDL1000; 0.96 parts ring-opening agent deionized water; 0.16 parts catalyst phosphoric acid; 0.14 parts antioxidant AT168; 0.32 parts chain extender 2,2'-(1,3-phenylene)-dioxazoline.

[0040] Preferably, Example 7 achieves the optimal performance ratio of tensile strength and elongation at break.

[0041] 19.42 parts caprolactam; 13.26 parts 1,10-sebacic acid; 7.00 parts isophorone diamine; 5.84 parts PTMG250; 1.17 parts PCDL3000; 0.97 parts ring-opening agent deionized water; 0.16 parts catalyst phosphoric acid; 0.14 parts antioxidant AT168; 0.31 parts chain extender 2,2'-(1,3-phenylene)-dioxazoline.

[0042] The preferred optimal performance ratio that achieves the highest hardness is Example 3:

[0043] 21.52 parts caprolactam; 12.33 parts 1,10-sebacic acid; 7.00 parts isophorone diamine; 4.67 parts PTMG250; 1.17 parts PCDL2000; 1.08 parts ring-opening agent deionized water; 0.16 parts catalyst phosphoric acid; 0.14 parts antioxidant AT168; 0.25 parts chain extender 2,2'-(1,3-phenylene)-dioxazoline.

[0044] The preferred optimal performance ratio that achieves the highest water absorption rate is Example 1:

[0045] 14.57 parts caprolactam; 13.45 parts 1,12-dodecanoic acid; 9.34 parts 4,4'-diaminodicyclohexylmethane; 7.00 parts PEG800; 2.33 parts PCDL500; 0.73 parts ring-opening agent deionized water; 0.12 parts catalyst p-toluenesulfonic acid; 0.12 parts antioxidant 1010; 0.12 parts antioxidant triphenyl phosphite; 0.26 parts chain extender 2,2'-(1,3-phenylene)-dioxazoline.

[0046] Beneficial effects:

[0047] Compared with the prior art, the beneficial effects of the present invention are:

[0048] 1. First, the transparent polyamide thermoplastic elastomer of the present invention uses caprolactam as the main raw material for its hard segments. It generates linear segments with dense amide group distribution through ring-opening polymerization. It then uses a certain proportion of long-chain dicarboxylic acid and aliphatic ring diamine for copolymerization. While maintaining the necessary hydrogen bond crosslinking density, it destroys the crystal regularity of single polycaprolactam, avoiding the problem of reduced light transmittance caused by high crystallinity of polyamide hard segments, thus maintaining high transparency of the material.

[0049] Secondly, the transparent polyamide thermoplastic elastomer of the present invention has soft segments composed of polyether diol and polycarbonate diol. The polycarbonate diol PCDL (molecular weight 500-3000) serves as an auxiliary soft segment. The carbonate groups in its molecular structure have high polarity and rigidity, and have good compatibility with the hard segments of polyamide. When combined with the highly flexible polyether diol segments, the two form a synergistic effect, which enables the soft segments to form semi-rigid amorphous regions at room temperature. The free movement of the soft segments is restricted to a certain extent, thereby improving the hardness, glass transition temperature and tensile strength of the material, while having little impact on elasticity.

[0050] Finally, the transparent copolyamide thermoplastic elastomer of the present invention incorporates the chain extender 2,2'-(1,3-phenylene)-dioxazoline, which further optimizes the chain segment connection efficiency. This chain extender reacts with terminal carboxyl groups on the molecular chain to form links between two molecular chains or to seal the molecular chains, making the molecular weight distribution of the material narrower, thereby improving the stability of the overall mechanical properties without having any negative impact on transparency.

[0051] 2. This invention uses caprolactam as the main raw material, which is conducive to the formation of hydrogen bond network in the molecular chain, so that the transparent thermoplastic elastomer has both rigidity and elasticity. In addition, caprolactam raw material is industrialized, has a stable source, and is inexpensive, which helps to reduce raw material costs.

[0052] 3. The polyether-polycarbonate-polyamide block copolymer of the present invention has high transparency, high tensile strength and high water absorption. It is prepared by one-pot melt polymerization, the synthesis process is simple and the reaction conditions are low. Only the feeding sequence, reaction temperature, nitrogen flow rate and stirring speed need to be controlled to obtain a stable product, which is easy to produce on a large scale.

[0053] 4. This invention introduces polycarbonate diol with a high glass transition temperature into polyether block polyamide thermoplastic elastomer, replacing some of the polyether soft segments with low glass transition temperatures. The dual soft segment compounding strategy overcomes the performance limitations of a single soft segment. Through the rigidity adjustment effect of polycarbonate diol, the hardness and tensile strength are significantly improved without sacrificing transparency. Although the elasticity is slightly reduced, the overall problem of "insufficient strength and toughness" in existing transparent TPAEs is solved, and the hardness and tensile strength of the material are improved.

[0054] 5. The addition of the chain extender 2,2'-(1,3-phenylene)-dioxazoline to this invention can effectively enhance the tensile properties of the polyether-polycarbonate-polyamide block copolymer without causing any negative impact on the transparency of the material.

[0055] 6. The polyether-polycarbonate-polyamide block copolymer prepared by the present invention has the potential for application in fields such as flexible electronic displays, transparent medical catheters, sports goggles, and transparent automotive parts due to its high transparency and good mechanical properties. Attached Figure Description

[0056] Figure 1 The infrared FT-IR spectrum of Example 7

[0057] Figure 2 These are tensile test diagrams from Examples 1 to 8.

[0058] Figure 3 This is a flowchart of the preparation process for obtaining highly transparent polyether-polycarbonate-polyamide block copolymers. Detailed Implementation

[0059] The present invention will be further described below with reference to the embodiments and the technical solutions in the embodiments. The described embodiments are only some embodiments of the present invention and do not constitute a limitation on other rights of the present invention.

[0060] In the various raw materials described in the embodiments, caprolactam has the highest mass proportion; the aliphatic cyclic diamine in the embodiments is 1,4-cyclohexanediamine, isophoronediamine, or 4,4'-diaminodicyclohexylmethane; the long-chain dicarboxylic acid in the embodiments is 1,10-sebacic acid or 1,12-dodecanoic acid; the polyether diol in the embodiments is polytetrahydrofuran (PTMG) or polyethylene glycol (PEG), with a molecular weight in the range of 250–1000; the polycarbonate diol (PCDL) in the embodiments is a carbonate group (-O) -CO-O-) is a linear polymer with repeating units and hydroxyl groups (-OH) at both ends. It belongs to polyester polyols and has a molecular weight in the range of 500 to 3000. In the embodiments, one or two of phosphoric acid and p-toluenesulfonic acid are selected as catalysts. In the embodiments, one or more of antioxidants 1010, antioxidant 1076, antioxidant AT168 and triphenyl phosphite are selected as antioxidants. In the embodiments, the chain extender is 2,2'-(1,3-phenylene)-dioxazoline.

[0061] The raw materials used in the embodiments of the present invention are as follows:

[0062] Caprolactam, AR, selected from Shanghai Maclean Biochemical Technology Co., Ltd.;

[0063] 1,4-Cyclohexanediamine, AR, selected from Shanghai Bid Pharmaceutical Technology Co., Ltd.;

[0064] Isophorone diamine, 99%, selected from Shanghai Myriel Biochemical Technology Co., Ltd.;

[0065] 4,4'-Diaminodicyclohexylmethane, 98%, selected from Shanghai Myriel Biochemical Technology Co., Ltd.;

[0066] 1,10-Sebacic acid, 99%, selected from Shanghai Myriel Biochemical Technology Co., Ltd.;

[0067] 1,12-Dodecanodicarboxylic acid, 99%, selected from Shanghai Myriel Biochemical Technology Co., Ltd.;

[0068] Polytetrahydrofuran (PTMG), CP, molecular weight 250, was selected from Shanghai Mairui Biochemical Technology Co., Ltd.

[0069] Polyethylene glycol (PEG) and CP, with molecular weights of 800 and 1000, were selected from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0070] Polycarbonate diols PCDL and CP, with molecular weights of 500, 1000, 2000, and 3000, are selected from Shanghai Mairui Biochemical Technology Co., Ltd.

[0071] Phosphoric acid, with a content >85%, was selected from Shanghai Dibai Biotechnology Co., Ltd.

[0072] p-Toluenesulfonic acid, 99%, selected from Shanghai Mairui Biochemical Technology Co., Ltd.;

[0073] Antioxidant 1010, AR, is selected from Shanghai Myriel Biochemical Technology Co., Ltd.;

[0074] Antioxidant 1076, AR, selected from Shanghai Yuanye Biotechnology Co., Ltd.

[0075] Antioxidant AT168, 98%, selected from TCI (Shanghai) Chemical Industry Development Co., Ltd.

[0076] Triphenyl phosphite, 98%, Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0077] 2,2'-(1,3-phenylene)-dioxazoline, 98%, selected from Shanghai Dibai Biotechnology Co., Ltd.

[0078] Example 1

[0079] This embodiment describes a method for synthesizing a polyether-polycarbonate-polyamide block copolymer, comprising the following steps:

[0080] Add 14.57 g of caprolactam, 9.34 g of 4,4-diaminodicyclohexylmethane, 13.45 g of 1,12-dodecanoic acid, 0.73 g of deionized water, 0.12 g of antioxidant 1010, 0.12 g of triphenyl phosphite, and 0.12 g of p-toluenesulfonic acid to a three-necked flask. Purge the air from the reaction flask with high-purity nitrogen, heat to 180°C, maintain a nitrogen flow rate of 10 mL / min and a stirring speed of 120 rpm, and maintain these conditions for 2 h. Then add 2.33 g of PCDL500 and 7.00 g of PEG800, heat to 250°C, maintain a nitrogen flow rate of 40 mL / min and a stirring speed of 135 rpm, and maintain these conditions for 2.5 h. Finally, 0.26 g of 2,2'-(1,3-phenylene)-dioxazoline was added, and the mixture was stirred at 135 r / min and reacted at 250 °C for 5 min. Then, nitrogen gas was removed, and a vacuum was drawn to -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250 °C for 1.5 h to obtain a highly transparent polyether-polycarbonate-polyamide block copolymer. The relevant test results are shown in Table 1, and the tensile stress-strain curve is shown in Appendix 1. Figure 2 .

[0081]

[0082] In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1 It is 2,2'-(1,3-phenylene)-dioxazoline, R 2 For PCDL500, A 2It is 1,12-dodecanedioic acid, R 1 For PEG800, A 1 It is 4,4'-diaminodicyclohexylmethane.

[0083] Example 2

[0084] This embodiment describes a method for synthesizing a polyether-polycarbonate-polyamide block copolymer, comprising the following steps:

[0085] Add 17.60 g caprolactam, 4.00 g 1,4-cyclohexanediamine, 10.75 g 1,12-dodecanoic acid, 0.88 g deionized water, 0.08 g antioxidant AT168, 0.08 g antioxidant 1076, 0.12 g phosphoric acid, and 0.10 g p-toluenesulfonic acid to a three-necked flask. Purge the air from the reaction flask with high-purity nitrogen, heat to 180°C, maintain a nitrogen flow rate of 10 mL / min and a stirring speed of 120 rpm, and maintain these conditions for 2 h. Then add 2.33 g PCDL500 and 7.20 g PEG1000, heat to 250°C, maintain a nitrogen flow rate of 40 mL / min and a stirring speed of 145 rpm, and maintain these conditions for 2.5 h. Finally, 0.19 g of 2,2'-(1,3-phenylene)-dioxazoline was added, the mixture was stirred at 145 r / min, and reacted at 250 °C for 5 min. Nitrogen gas was then removed, and a vacuum was applied to a reading of -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250 °C for 1.5 h to obtain a highly transparent polyether-polycarbonate-polyamide block copolymer. Relevant test results are shown in Table 1, and the tensile stress-strain curve is shown in Appendix 1. Figure 2 .

[0086] The high-transparency polyether-polycarbonate-polyamide block copolymer described in Example 2 has the following structural formula:

[0087]

[0088] In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1 It is 2,2'-(1,3-phenylene)-dioxazoline, R 2 For PCDL500, A 2 It is 1,12-dodecanedioic acid, R 1 For PEG1000, A 1 It is 1,4-cyclohexanediamine.

[0089] Example 3

[0090] This embodiment describes a method for synthesizing a polyether-polycarbonate-polyamide block copolymer, comprising the following steps:

[0091] Add 21.52 g caprolactam, 7.00 g isophorone diamine, 12.33 g 1,10-sebacic acid, 1.08 g deionized water, 0.14 g antioxidant AT168, and 0.16 g phosphoric acid to a three-necked flask. Purge the air from the reaction flask with high-purity nitrogen, heat to 180°C, maintain a nitrogen flow rate of 10 mL / min and a stirring speed of 120 rpm, and maintain these conditions for 2 h. Then add 1.17 g PCDL2000 and 4.67 g PTMG250, heat to 250°C, maintain a nitrogen flow rate of 40 mL / min and a stirring speed of 135 rpm, and maintain these conditions for 2.5 h. Finally, 0.26 g of 2,2'-(1,3-phenylene)-dioxazoline was added, the mixture was stirred at 135 r / min, and reacted at 250 °C for 5 min. Nitrogen gas was then removed, and a vacuum was applied to a reading of -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250 °C for 1.5 h to obtain a highly transparent polyether-polycarbonate-polyamide block copolymer. Relevant test results are shown in Table 1, and the tensile stress-strain curve is shown in Appendix 1. Figure 2 .

[0092] The high-transparency polyether-polycarbonate-polyamide block copolymer described in Example 3 has the following structural formula:

[0093]

[0094] In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1 It is 2,2'-(1,3-phenylene)-dioxazoline, R 2 For PCDL2000, A 2 It is 1,10-sebacic acid, R 1 For PTMG250, A 1 It is isophorone diamine.

[0095] Example 4

[0096] This embodiment describes a method for synthesizing a polyether-polycarbonate-polyamide block copolymer, comprising the following steps: Adding 19.03 g of caprolactam, 7.00 g of isophorone diamine, 13.67 g of 1,10-sebacic acid, 0.95 g of deionized water, 0.14 g of antioxidant AT168, and 0.16 g of phosphoric acid to a three-necked flask; purging the air in the reaction flask with high-purity nitrogen; heating to 180°C; maintaining a nitrogen flow rate of 10 mL / min and a stirring speed of 120 r / min; and maintaining these conditions for 2 h. Subsequently, adding 1.17 g of PCDL500 and 5.84 g of PTMG250; heating to 250°C; maintaining a nitrogen flow rate of 40 mL / min and a stirring speed of 145 r / min; and maintaining these conditions for 2.5 h. Finally, 0.33 g of 2,2'-(1,3-phenylene)-dioxazoline was added, the mixture was stirred at 145 r / min, and reacted at 250 °C for 5 min. Nitrogen gas was then removed, and a vacuum was applied to a reading of -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250 °C for 1.5 h to obtain a highly transparent polyether-polycarbonate-polyamide block copolymer. Relevant test results are shown in Table 1, and the tensile stress-strain curve is shown in Appendix 1. Figure 2 .

[0097] The high-transparency polyether-polycarbonate-polyamide block copolymer described in Example 4 has the following structural formula:

[0098]

[0099] In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1 It is 2,2'-(1,3-phenylene)-dioxazoline, R 2 For PCDL500, A 2 It is 1,10-sebacic acid, R 1 For PTMG250, A 1 It is isophorone diamine.

[0100] Example 5

[0101] This embodiment describes a method for synthesizing a polyether-polycarbonate-polyamide block copolymer, comprising the following steps: Adding 19.28 g of caprolactam, 7.00 g of isophorone diamine, 13.42 g of 1,10-sebacic acid, 0.96 g of deionized water, 0.14 g of antioxidant AT168, and 0.16 g of phosphoric acid to a three-necked flask; purging the flask with high-purity nitrogen to replace the air; heating to 180°C; maintaining a nitrogen flow rate of 10 mL / min and a stirring speed of 120 r / min; and maintaining these conditions for 2 hours. Subsequently, adding 1.17 g of PCDL500 and 5.84 g of PTMG250; heating to 250°C; maintaining a nitrogen flow rate of 40 mL / min and a stirring speed of 145 r / min; and maintaining these conditions for 2.5 hours. Finally, 0.33 g of 2,2'-(1,3-phenylene)-dioxazoline was added, the mixture was stirred at 145 r / min, and reacted at 250 °C for 5 min. Nitrogen gas was then removed, and a vacuum was applied to a reading of -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250 °C for 1.5 h to obtain a highly transparent polyether-polycarbonate-polyamide block copolymer. Relevant test results are shown in Table 2, and the tensile stress-strain curve is attached. Figure 2 .

[0102] The high-transparency polyether-polycarbonate-polyamide block copolymer described in Example 5 has the following structural formula:

[0103]

[0104] In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1 It is 2,2'-(1,3-phenylene)-dioxazoline, R 2 For PCDL1000, A 2 It is 1,10-sebacic acid, R 1 For PTMG250, A 1 It is isophorone diamine.

[0105] Example 6

[0106] This embodiment describes a method for synthesizing a polyether-polycarbonate-polyamide block copolymer, comprising the following steps: Adding 19.38 g of caprolactam, 7.00 g of isophorone diamine, 13.30 g of 1,10-sebacic acid, 0.97 g of deionized water, 0.14 g of antioxidant AT168, and 0.16 g of phosphoric acid to a three-necked flask; purging the air in the reaction flask with high-purity nitrogen; heating to 180°C; maintaining a nitrogen flow rate of 10 mL / min and a stirring speed of 120 r / min; and maintaining these conditions for 2 h. Subsequently, adding 1.17 g of PCDL2000 and 5.84 g of PTMG250; heating to 250°C; maintaining a nitrogen flow rate of 40 mL / min and a stirring speed of 145 r / min; and maintaining these conditions for 2.5 h. Finally, 0.31 g of 2,2'-(1,3-phenylene)-dioxazoline was added, and the mixture was stirred at 145 r / min and reacted at 250 °C for 5 min. Nitrogen gas was then removed, and a vacuum was applied to a reading of -0.1 MPa. The mixture was then stirred at 100 r / min and reacted at 250 °C for 1.5 h to obtain a highly transparent polyether-polycarbonate-polyamide block copolymer. Relevant test results are shown in Table 2, and the tensile stress-strain curve is attached. Figure 2 .

[0107] The high-transparency polyether-polycarbonate-polyamide block copolymer described in Example 6 has the following structural formula:

[0108]

[0109] In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1 It is 2,2'-(1,3-phenylene)-dioxazoline, R 2 For PCDL2000, A 2 It is 1,10-sebacic acid, R 1 For PTMG250, A 1 It is isophorone diamine.

[0110] Example 7

[0111] This embodiment describes a method for synthesizing a polyether-polycarbonate-polyamide block copolymer, comprising the following steps: Adding 19.42 g of caprolactam, 7.00 g of isophorone diamine, 13.26 g of 1,10-sebacic acid, 0.97 g of deionized water, 0.14 g of antioxidant AT168, and 0.16 g of phosphoric acid to a three-necked flask; purging the air in the reaction flask with high-purity nitrogen; heating to 180°C; maintaining a nitrogen flow rate of 10 mL / min and a stirring speed of 120 r / min; and maintaining these conditions for 2 h. Subsequently, adding 1.17 g of PCDL3000 and 5.84 g of PTMG250; heating to 250°C; maintaining a nitrogen flow rate of 40 mL / min and a stirring speed of 145 r / min; and maintaining these conditions for 2.5 h. Finally, 0.31 g of 2,2'-(1,3-phenylene)-dioxazoline was added, the mixture was stirred at 145 r / min, and reacted at 250 °C for 5 min. Nitrogen gas was removed and the pressure was evacuated to -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250 °C for 1.5 h to obtain a highly transparent polyether-polycarbonate-polyamide block copolymer.

[0112] The high-transparency polyether-polycarbonate-polyamide block copolymer described in Example 7 has the following structural formula:

[0113]

[0114] In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1 It is 2,2'-(1,3-phenylene)-dioxazoline, R 2 For PCDL3000, A 2 It is 1,10-sebacic acid, R 1 For PTMG250, A 1 It is isophorone diamine. The relevant test results for Example 7 are shown in Table 2, and the tensile stress-strain curves are shown in the appendix. Figure 2 Infrared spectral characterization is shown in the appendix. Figure 1 Appendix Figure 1 1637.84cm -1 (Amide I band, C=O stretching) and 1543.59cm -1 The absorption peak (amide II band, NH bending + CN stretching) indicates the formation of amide bonds in the system, a key characteristic of polyamide segments; it appears at 1110.61 cm⁻¹. -1 The absorption peak (stretching vibration of COC) suggests the presence of ether bonds or carbonate structures; at 2925.27 cm⁻¹ -1 (CH2 asymmetric stretching), 2855.82cm -1 (CH2 symmetrical stretching) and 726.01cm -1The absorption peak (long-chain CH2 in-plane rocking) indicates the presence of a corresponding long carbon chain structure in the system, which is consistent with the long-chain structures of sebacic acid, PCDL3000, and PTMG250 in the raw materials; no absorption peak was observed in the 3200–3600 cm⁻¹ range. -1 The broad absorption peak (characteristic absorption peak of hydroxyl group) indicates that PCDL3000 and PTMG250 in the main raw materials have fully participated in the reaction. The above analysis of the infrared spectrum shows that the target product has been successfully synthesized.

[0115] Example 8

[0116] This embodiment describes a method for synthesizing a polyether-polycarbonate-polyamide block copolymer, comprising the following steps: Adding 16.88 g of caprolactam, 7.00 g of isophorone diamine, 13.64 g of 1,10-sebacic acid, 0.84 g of deionized water, 0.14 g of antioxidant AT168, and 0.16 g of phosphoric acid to a three-necked flask; purging the air in the reaction flask with high-purity nitrogen; heating to 180°C; maintaining a nitrogen flow rate of 10 mL / min and a stirring speed of 120 r / min; and maintaining these conditions for 2 h. Subsequently, adding 1.17 g of PCDL500 and 7.00 g of PTMG250; heating to 250°C; maintaining a nitrogen flow rate of 40 mL / min and a stirring speed of 145 r / min; and maintaining these conditions for 2.5 h. Finally, 0.39 g of 2,2'-(1,3-phenylene)-dioxazoline was added, the mixture was stirred at 145 r / min, and reacted at 250 °C for 5 min. Nitrogen gas was then removed, and a vacuum was applied to a reading of -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250 °C for 1.5 h to obtain a highly transparent polyether-polycarbonate-polyamide block copolymer. Relevant test results are shown in Table 2, and the tensile stress-strain curve is attached. Figure 2 The high-transparency polyether-polycarbonate-polyamide block copolymer described in Example 8 has the following structural formula:

[0117]

[0118] In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1 It is 2,2'-(1,3-phenylene)-dioxazoline, R 2 For PCDL500, A 2 It is 1,10-sebacic acid, R 1 For PTMG250, A 1 It is isophorone diamine.

[0119] Comparative Example 1

[0120] The method for synthesizing a polyether-polyamide block copolymer, as shown in this comparative example, includes the following steps: 18.71 g of caprolactam, 7.00 g of isophorone diamine, and 13.98 g of 1,10-sebacic acid were added to a three-necked flask, along with the ring-opening agent, antioxidant, and catalyst formulation listed in Table 3. High-purity nitrogen was introduced to replace the air in the reaction flask, and the mixture was heated to 180°C. The nitrogen flow rate was maintained at 10 mL / min, and the stirring speed was 120 r / min. The reaction was maintained under these conditions for 2 h. Subsequently, 7.00 g of PTMG250 was added, and the mixture was heated to 250°C. The nitrogen flow rate was maintained at 40 mL / min, and the stirring speed was 145 r / min. The reaction was maintained under these conditions for 2.5 h. Finally, the nitrogen was removed, and a vacuum was applied to -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250°C for 45 min to obtain a highly transparent polyether-polyamide block copolymer. The relevant test results are shown in Table 3.

[0121] Comparative Example 2

[0122] The method for synthesizing a polyether-polyamide block copolymer, as shown in this comparative example, includes the following steps: 20.82 g of caprolactam, 7.00 g of isophorone diamine, and 13.04 g of 1,10-sebacic acid were added to a three-necked flask, along with the ring-opening agent, antioxidant, and catalyst formulation listed in Table 3. High-purity nitrogen was introduced to replace the air in the reaction flask, and the mixture was heated to 180°C. The nitrogen flow rate was maintained at 10 mL / min, and the stirring speed was 120 r / min. The reaction was maintained under these conditions for 2 h. Subsequently, 5.84 g of PTMG250 was added, and the mixture was heated to 250°C. The nitrogen flow rate was maintained at 40 mL / min, and the stirring speed was 135 r / min. The reaction was maintained under these conditions for 2.5 h. Finally, the nitrogen was removed, and a vacuum was applied to -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250°C for 45 min to obtain a highly transparent polyether-polyamide block copolymer. The relevant test results are shown in Table 3.

[0123] Comparative Example 3

[0124] The comparative example describes a method for synthesizing a polyether-polyamide block copolymer, comprising the following steps: Adding 18.68 g of caprolactam, 7.00 g of isophorone diamine, and 14.15 g of 1,10-sebacic acid to a three-necked flask, along with the ring-opening agent, antioxidant, and catalyst formulation listed in Table 3. Purge the air from the reaction flask with high-purity nitrogen, heat to 180°C, maintain a nitrogen flow rate of 10 mL / min, and a stirring speed of 120 r / min, and maintain these conditions for 2 h. Subsequently, adding 7.00 g of PTMG250, heating to 250°C, maintaining a nitrogen flow rate of 40 mL / min, and a stirring speed of 145 r / min, and maintaining these conditions for 2.5 h. Finally, the nitrogen gas was removed, and 0.36 g of 2,2'-(1,3-phenylene)-dioxazoline was added. The mixture was stirred at 145 r / min and reacted at 250 °C for 5 min. The nitrogen gas was then removed and the vacuum was evacuated to -0.1 MPa. The mixture was stirred at 100 r / min and reacted at 250 °C for 45 min to obtain a highly transparent polyether-polyamide block copolymer. The relevant test results are shown in Table 3.

[0125] Comparative Example 4

[0126] The comparative example describes a method for synthesizing a polyether-polyamide block copolymer, comprising the following steps: Adding 20.68 g of caprolactam, 7.00 g of isophorone diamine, and 13.18 g of 1,10-sebacic acid to a three-necked flask, along with the ring-opening agent, antioxidant, and catalyst formulation listed in Table 3. Purge the air from the reaction flask with high-purity nitrogen, heat to 180°C, maintain a nitrogen flow rate of 10 mL / min, and a stirring speed of 120 r / min, and maintain these conditions for 2 h. Subsequently, adding 5.84 g of PTMG250, heating to 250°C, maintaining a nitrogen flow rate of 40 mL / min, and a stirring speed of 135 r / min, and maintaining these conditions for 2.5 h. Finally, nitrogen gas was removed, and 0.30 g of 2,2'-(1,3-phenylene)-dioxazoline was added. The mixture was stirred at 135 r / min and reacted at 250 °C for 5 min. The vacuum was then drawn to -0.1 MPa, and the mixture was stirred at 100 r / min and reacted at 250 °C for 45 min to obtain a highly transparent polyether-polyamide block copolymer. The relevant test results are shown in Table 3.

[0127] Table 1. Summary of raw material composition and copolymer properties in Examples 1-4

[0128]

[0129]

[0130] Table 2. Summary of raw material composition and copolymer properties in Examples 5-8

[0131]

[0132]

[0133] Table 3. Summary of raw material composition and copolymer properties of Comparative Examples 1-4

[0134]

[0135]

[0136]

[0137] The performance testing methods and standards in this invention are as follows:

[0138] Tensile properties: Tested according to GB / T1040.1-2018 standard, the testing instrument model is Zhuhai Sansitaijie Electrical Equipment Co., Ltd.'s universal material testing machine CMT-4304, the specimen type is 5A as specified in GB / T1040.2-2022, and the tensile rate is 50mm / min;

[0139] Transmittance: The test instrument was an LS117 optical density meter from Shenzhen Linshang Technology Co., Ltd. Each sample was measured three times at a thickness of about 2 mm, and the average value was taken.

[0140] Water absorption rate: Tested according to GB / T1034-2008 standard, using method 1: determination of water absorption in water at 23℃;

[0141] Hardness: Tested according to GB / T 2411-2008 standard, using Dongguan Sanliang Measuring Tools Co., Ltd.'s Shore hardness tester LXD-D, each sample was tested five times and the average value was taken;

[0142] Glass transition temperature: The Pyris 1DSC differential scanning calorimeter from PerkinElmer, USA, was used to obtain the secondary heating curve at a heating rate of 20℃ / min.

[0143] Fourier transform infrared spectroscopy (FT-IR) characterization: A Nicolet IS50 infrared spectrometer from Thermo Fisher Scientific, USA, in ATR mode, was used, with 32 acquisitions for both background and sample data.

[0144] From Table 1 and Table 2, we can see that:

[0145] The polyether-polycarbonate-polyamide block copolymers prepared in Examples 1-8 all have good transparency, with a minimum light transmittance of 85% and a maximum of over 91%, and good mechanical properties, with tensile strength exceeding 18 MPa and a maximum of 54.70 MPa, and elongation at break exceeding 240% and a maximum of 423%.

[0146] As shown in Examples 4-7, the polyether-polycarbonate-polyamide block copolymers with PTMG250 content of 12.5 wt% and PCDL content of 2.5 wt% all exhibit good properties. The differences between polycarbonate diols of different molecular weights are very small under the same proportion. Example 7, which uses PCDL3000, has the best overall performance, with a tensile strength of 54.70 MPa, an elongation at break of 276.1%, a yield strength of 29.59 MPa, a light transmittance of 88.10%, a water absorption rate of 4.70%, a hardness of 81.5 Shore D, and a glass transition temperature of 29.94 °C.

[0147] Comparing Examples 4 and 8, it can be seen that, within a certain range, the elongation at break of the polymer increases with the increase of the proportion of PTMG250, while the yield strength and tensile strength decrease, and the change in transparency is very small and can be ignored.

[0148] As shown in Example 4, Comparative Example 1, and Comparative Example 3, replacing part of the polyether in the polyether-polyamide block copolymer with polycarbonate diol and adding the chain extender 2,2'-(1,3-phenylene)-dioxazoline resulted in a polyether-polycarbonate-polyamide block copolymer with superior overall properties. The yield strength increased from 10.56 MPa in Comparative Example 1 and 13.32 MPa in Comparative Example 3 to 26.85 MPa in Example 4; the hardness increased from 74.5 Shore D in Comparative Example 1 and 73.0 Shore D in Comparative Example 3 to 78.5 Shore D in Example 4; and the glass transition temperature increased from 23.80 °C in Comparative Example 1 and 26.32 °C in Comparative Example 3 to 29.26 °C in Example 4. The tensile strengths of the three were similar, all around 50 MPa, and the light transmittance all exceeded 90%.

[0149] As shown in Comparative Examples 2 and 4, the addition of chain extender 2,2'-(1,3-phenylene)-dioxazoline can improve the tensile strength, yield strength, and glass transition temperature of the block copolymer. The PTMG250 content in both comparative examples was 15.0 wt%. The tensile strength of the product of Comparative Example 4, which only added 0.36 g of chain extender, increased from 49.79 MPa in Comparative Example 2 to 54.92 MPa, the yield strength increased from 28.53 MPa in Comparative Example 2 to 30.81 MPa, and the glass transition temperature increased from 30.94℃ in Comparative Example 2 to 33.02℃. The elongation at break of Comparative Example 4 was slightly lower than that of Comparative Example 2, and the change in transparency was very small, both above 90%.

[0150] Currently, almost none of the publicly disclosed invention patents involve the synthesis of highly transparent polyether-polycarbonate-polyamide block copolymers with caprolactam as the main raw material. Most of the disclosed synthesis methods use long-chain dicarboxylic acids and aliphatic cyclic diamines as polyamide segments and polyether segments to alternately copolymerize and prepare transparent polyamide thermoplastic elastomers. The raw material costs are relatively high, and there are disadvantages such as complex reaction steps, poor mechanical properties of the product, and poor transparency, which are not conducive to large-scale production and commercialization.

[0151] This invention proposes a block copolymer elastomer material using caprolactam, aliphatic cyclic diamine, and long-chain diacid as the hard segments of the polyamide, and polyether diol and polycarbonate diol as the soft segments. This material achieves both high light transmittance and excellent mechanical properties. Utilizing inexpensive and widely available caprolactam as the main raw material, partially replacing polyether diol with polycarbonate diol, and adding a small amount of chain extender 2,2'-(1,3-phenylene)-dioxazoline, this invention improves the tensile strength, hardness, and glass transition temperature of the material while maintaining high transparency, with only a slight impact on the material's elasticity, resulting in excellent overall performance.

[0152] The high-transparency polyether-polycarbonate-polyamide block copolymer described in this invention can be obtained by one-pot melt polymerization. The raw materials are readily available, the synthesis steps are simple, and it is easy to industrialize. In the future, it is expected to be widely used in flexible electronic displays, transparent medical catheters, sports goggles, transparent automotive parts, and other fields.

[0153] The technical features of the above embodiments can be combined arbitrarily. This document only illustrates several implementation methods of this patent and is not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this invention should be within the protection scope of this invention. Those skilled in the art can make various changes or modifications within the scope of the claims, which do not affect the substantive content of this invention.

[0154] The present invention is not limited to the specific technical solutions described in the above embodiments. All technical solutions formed by equivalent substitutions are within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a highly transparent polyether-polycarbonate-polyamide block copolymer, characterized in that, The highly transparent polyether-polycarbonate-polyamide block copolymer is produced by one-pot melt polymerization of caprolactam, long-chain dicarboxylic acid, aliphatic cyclic diamine, polyether diol, and polycarbonate diol PCDL (molecular weight 500-3000) as raw materials in the presence of ring-opening agent, catalyst, antioxidant, and chain extender 2,2'-(1,3-phenylene)-dioxazoline or 1,4-bis(4,5-dihydro-2-oxazole)benzene. The highly transparent polyether-polycarbonate-polyamide block copolymer has the following structural formula: In the formula, n = 10 ~ 150, x = 2 ~ 10, K 1 It is 2,2'-(1,3-phenylene)-dioxazoline or 1,4-bis(4,5-dihydro-2-oxazol)benzene, R 2 For polycarbonate diol PCDL, A 2 R is a long-chain dicarboxylic acid, represented by 1,10-sebacic acid or 1,12-dodecanoic acid. 1 It is polytetrahydrofuran diol (PTMG) or polyethylene glycol (PEG), A 1 It is 1,4-cyclohexanediamine, isophoronediamine, or 4,4'-diaminodicyclohexylmethane.

2. The method for preparing the high-transparency polyether-polycarbonate-polyamide block copolymer according to claim 1, characterized in that, Polycarbonate diol (PCDL) has the following structural formula: Where y = 2 to 23; The chain extender 2,2'-(1,3-phenylene)-dioxazoline has the following structural formula: The structural formula of 4-bis(4,5-dihydro-2-oxazole)benzene is:

3. The method for preparing the high-transparency polyether-polycarbonate-polyamide block copolymer according to claim 1, characterized in that: The long-chain dicarboxylic acid is one or more of 1,10-sebacic acid or 1,12-dodecanoic acid; the aliphatic cyclic diamine is 1,4-cyclohexanediamine, isophoronediamine, or 4,4'-diaminodicyclohexylmethane; the polyether diol is one or two of polytetrahydrofuran diol (PTMG) or polyethylene glycol (PEG), with a molecular weight of 250-1000; the ring-opening agent is deionized water; the catalyst is one or two of phosphoric acid and p-toluenesulfonic acid; the antioxidant is one or more of antioxidant AT-168, antioxidant 1010, antioxidant 1076, or triphenyl phosphite.

4. The method for preparing the high-transparency polyether-polycarbonate-polyamide block copolymer according to claim 1, characterized in that: The mass fractions of each raw material during synthesis are as follows: 14.57–21.52 parts of caprolactam; 10.75–14.64 parts of long-chain dicarboxylic acid; 4.00–9.34 parts of alicyclic diamine; 4.67–7.20 parts of polyether diol; and 1.17–2.33 parts of polycarbonate diol. The amount of the long-chain dicarboxylic acid is equal to the sum of the amounts of the alicyclic diamine, polyether diol, and polycarbonate diol, plus half the amount of the chain extender.

5. The method for preparing the high-transparency polyether-polycarbonate-polyamide block copolymer according to claim 1, characterized in that: The ring-opening agent is used at a mass fraction of 5.0–6.0% of caprolactam; the chain extender is used at a mass fraction of 0.6%–0.9% of the sum of the amounts of polyether diol and polycarbonate diol; the catalyst is used at a mass fraction of 0.3–0.5% of the polymer raw material; and the antioxidant is used at a mass fraction of 0.1–0.5% of the polymer raw material.

6. The method for preparing the high-transparency polyether-polycarbonate-polyamide block copolymer according to claim 1, characterized in that: The optimal mass ratio for achieving high transparency, tensile strength, and elongation at break is: 19.42 parts caprolactam; 13.26 parts 1,10-sebacic acid; 7.00 parts isophorone diamine; 5.84 parts PTMG250; 1.17 parts PCDL3000; 0.97 parts ring-opening agent (deionized water); 0.16 parts catalyst (phosphoric acid); 0.14 parts antioxidant (AT168). 0.31 parts of chain extender 2,2'-(1,3-phenylene)-dioxazoline.

7. The method for preparing the high-transparency polyether-polycarbonate-polyamide block copolymer according to claim 1, characterized in that: Includes the following steps: (1) Add the required caprolactam, long-chain dicarboxylic acid, aliphatic ring diamine, catalyst, ring-opening agent and antioxidant to a 250mL three-necked flask. Under nitrogen protection at a flow rate of 10mL / min, heat to 180-200℃. After the raw materials in the flask are completely melted, start stirring at a speed of 100-120r / min. Maintain this condition for 2 hours. The small molecules produced by the reaction are distilled out through the condenser of the distillation head. (3) Add the polyether diol and polycarbonate diol to a three-necked flask, heat to 240-260°C, nitrogen flow rate between 20-40 mL / min, stirring speed between 120-160 r / min, and maintain these conditions to continue the reaction for 2-2.5 hours. (4) Add the chain extender to a three-necked flask, react at 240–260°C for 5 minutes, then turn off the nitrogen gas, adjust the stirring speed to 90–110 r / min, and evacuate to a pressure of -0.1 kJ / min. A highly transparent polyether-polycarbonate-polyamide block copolymer can be obtained by reacting at MPa and temperature of 240-260℃ for 1-2 hours.

8. The highly transparent polyether-polycarbonate-polyamide block copolymer prepared according to any one of claims 1 to 7.

9. The application of the high-transparency polyether-polycarbonate-polyamide block copolymer according to claim 8, characterized in that: It can be used in aircraft or high-speed rail windows, sports goggles, flexible displays, and medical catheters.

Citation Information

Patent Citations

  • Transparent thermoplastic polyamide elastomer and preparation method thereof

    CN108299639A